Data Driven Second Integral Sliding Mode Control for the Digital Phase-Locked Loop - Haiqin Liu; Mingdong Hou; Guangye Li; Renming Yang; Yun Zhang (IEEE Access)
The high accuracy and flexibility of the digital phase-locked loop (DPLL) make it a versatile tool with a wide range of applications in modern sensor technology. This article designs a new controller based on the traditional SOGI-PLL (second-order generalized integral phase-locked loop) and the Ultra-Local Model (ULM). The proposed algorithm does not rely on the detailed structure of each part of the PLL, but instead uses a ULM to replace the PLL structure and closed-loop loop. Firstly, the unknown disturbance of the ULM is estimated through a finite-time stability observer (FSO). Then, a discrete-time second integral sliding-mode controller (DSISMC) is designed based on the integral sliding surface, and the DPLL model is corrected offline using the obtained data. The theoretical results are mathematically rigorously proved, and the results of the simulation study show that the proposed method exhibits faster and superior performance in signal estimation and tracking compared to traditional PID algorithms.